2020
DOI: 10.1186/s12887-020-1923-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival and ocular preservation in a long-term cohort of Japanese patients with retinoblastoma

Abstract: Background: Retinoblastoma is an ocular tumor in infants with cancer predisposition. Treatment of the rare tumor needs to be optimized for ocular preserved survival without second primary malignancy (SPM). Methods: We studied the outcomes of all patients with retinoblastoma at a tertiary center in 1984-2016, when preservation method changed from radiotherapy (1984-2001) to systemic chemotherapy (2002-2016). Results: One-hundred sixteen infants developed unilateral-(n = 77), bilateral-(n = 38), or trilateral-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(28 reference statements)
1
9
0
1
Order By: Relevance
“…However, they had higher risk of developing a second primary neoplasm. 14 Thus long term follow up, proper counseling of caregivers and rehabilitation are crucial for these disabled individuals. The outcome of the present study will help policy makers in Saudi Arabia to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, they had higher risk of developing a second primary neoplasm. 14 Thus long term follow up, proper counseling of caregivers and rehabilitation are crucial for these disabled individuals. The outcome of the present study will help policy makers in Saudi Arabia to address these issues.…”
Section: Discussionmentioning
confidence: 99%
“…The group described is small but the reason for the significant difference cannot be explained so far. Anyhow, no significant differences were seen between these above described groups for overall 10-year survival [ 68 ].…”
Section: Causes Of Smn Developmentmentioning
confidence: 99%
“…In a single-centre study done in the USA (1994–2014), 4 the retinoblastoma survival rate was reported to reach 99% (mean follow-up 4–8 years, depending on age group); in a single-centre study done in the UK (2002–14), 5 it was reported to reach 100% (mean follow-up 5 years); and in a single-centre study done in Japan (1984–2016), 6 it was reported to reach 95% (10-year overall survival), with most deaths occurring from trilateral retinoblastoma in all three studies. In low-income countries, survival rates are significantly lower: 60% (5-year survival) in a single-centre study done in Uganda (2009–19), 7 53% (follow-up time not indicated) in a single-centre study done in Senegal (2006–10), 8 and 24% (10-year survival) in a single-centre study done in Nepal (1998–2008), 9 with the majority of deaths in all three studies occurring from metastatic spread.…”
Section: Introductionmentioning
confidence: 98%